Comparison between adaptive and fixed stimulus paired-pulse transcranial magnetic stimulation (ppTMS) in normal subjects - Amandusson, Å.; Flink, R.; Axelson, H.W. (Clinical neurophysiology practice, 2017)
•Excitability indices from adaptive paired-pulse TMS correlated to those of fixed-stimulus ppTMS.•Floor/ceiling effects in fixed-stimulus ppTMS excitability data did not occur with adaptive ppTMS.•Adaptive ppTMS seems to be more sensitive in detecting changes in cortical inhibition. Paired-pulse TMS (ppTMS) examines cortical excitability but may require lengthy test procedures and fine tuning of stimulus parameters due to the inherent variability of the elicited motor evoked potentials (MEPs) and their tendency to exhibit a ‘ceiling/floor effects’ in inhibition trials. Aiming to overcome some of these limitations, we implemented an ‘adaptive’ ppTMS protocol and compared the obtained excitability indices with those from ‘conventional’ fixed-stimulus ppTMS. Short- and long interval intracortical inhibition (SICI and LICI) as well as intracortical facilitation (ICF) were examined in 20 healthy subjects by adaptive ppTMS and fixed-stimulus ppTMS. The test stimulus intensity was either adapted to produce 500μVMEPs (by a maximum likelihood strategy in combination with parameter estimation by sequential testing) or fixed to 120% of resting motor threshold (rMT). The conditioning stimulus was 80% rMT for SICI and ICF and 120% MT for LICI in both tests. There were significant (p<0.05) intraindividual correlations between the two methods for all excitability measures. There was a clustering of SICI and LICI indices near maximal inhibition (‘ceiling effect’) in fixed-stimulus ppTMS which was not observed for adaptive SICI and LICI. Adaptive ppTMS excitability data correlates to those acquired from fixed-stimulus ppTMS. Adaptive ppTMS is easy to implement and may serve as a more sensitive method to detect changes in cortical inhibition than fixed stimulus ppTMS. Whether equally confident data are produced by less stimuli with our adaptive approach (as already confirmed for motor threshold estimation) remains to be explored.